1988
DOI: 10.1111/j.1399-3054.1988.tb02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase activity decay and energy supply in Frankia after addition of ammonium to the host plant Alnus incana

Abstract: A clone of Alnus incana (L.) Moench was grown in symbiosis with a local source of Frankia or with Frankia Ar14. Seven to 9‐week‐old plants were given 20 mM NH4Cl (20 mM KCl = control) for 3 days. Nitrogenase activity of intact plants decreased gradually within the 3 days of treatment to about 10% of the initial rates. Hydrogen evolution in air and total nitrogenase activity responded similarly to the treatment. Relative efficiency of nitrogenase thus remained the same throughout the study period. Control plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…1) corroborates earlier studies which indicated that the loss of in vivo activity in response to plant stress was due to loss of active nitrogenase rather than shortage of reductant and ATP (8,10,22). Loss of active nitrogenase was concluded since the nitrogenase activity of nodule homogenates, supplemented with dithionite and Mg-ATP, from treated plants were inhibited compared with control plants.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1) corroborates earlier studies which indicated that the loss of in vivo activity in response to plant stress was due to loss of active nitrogenase rather than shortage of reductant and ATP (8,10,22). Loss of active nitrogenase was concluded since the nitrogenase activity of nodule homogenates, supplemented with dithionite and Mg-ATP, from treated plants were inhibited compared with control plants.…”
Section: Discussionsupporting
confidence: 78%
“…This was the case for Frankia-Alnus symbioses after addition of ammonium (8, 1 1), drought stress (22), darkening and defoliation (10,25), and decreased temperature (12). In some of these studies, nitrogenase activity of intact plants (in vivo) and nitrogenase activity in vitro were measured (8,10,22). In vitro activity was measured on root nodule homogenates supplied with Mg-ATP and the electron donor dithionite.…”
mentioning
confidence: 99%
“…Mechanisms for decreased nitrogenase activity following additions of nitrate to legumes have been proposed to involve either carbohydrate deprivation of nodules or nitrite inhibition of nitrogenase activity (see Parsons et al, 1993 for review). In the case of addition of ammonium to Alnus incana, decreased nitrogenase activity could not be explained solely by limited energy supply to nitrogenase (Huss-Danell & Hahlin, 1988), and, of course, any theories on nitrite effects are not relevant to ammonium treatments. Recently, a mechanism involving feedback of phloem N on nitrogenase activity was proposed for legume nodules (Parsons et al, 1993).…”
Section: Mineral Nutritionmentioning
confidence: 97%
“…From the earliest studies N was reported to inhibit Ng fixation in actinorhizal nodules (Rodriguez-Barrueco, Mackintosh & Bond, 1970). In Alnus incana, both total nitrogenase activity and nitrogenase-catalysed Hg evolution were decreased by additions of ammonium (Huss-Danell et al, 19826;Huss-Danell & Hahlin, 1988). The decreased activity measured in intact plants was accompanied by degradation of vesicles (Huss-Danell et al, 19826) and loss of active nitrogenase (Huss-Danell & Hahlin, 1988).…”
Section: Mineral Nutritionmentioning
confidence: 99%
“…Symbiotic N 2 fixation decreases in Alnus spp. subjected experimentally to high concentrations of N (Huss- Danell and Hahlin 1988). However, small, incremental N additions may maintain or even stimulate fixation in Alnus spp.…”
Section: Introductionmentioning
confidence: 99%